Late Paleocene–early Eocene Arctic Ocean sea surface temperatures: reassessing biomarker paleothermometry at Lomonosov Ridge - A. Sluijs; J. Frieling; G. N. Inglis; K. G. J. Nierop; F. Peterse; F. Sangiorgi; S. Schouten (Climate of the Past, 2020)
A series of papers published shortly after the Integrated Ocean Drilling Program Arctic Coring Expedition (ACEX, 2004) on Lomonosov Ridge indicated remarkably high early Eocene sea surface temperatures (SSTs; ca. 23 to 27 ∘ C) and land air temperatures (ca. 17 to 25 ∘ C) based on the distribution of isoprenoid and branched glycerol dialkyl glycerol tetraether (isoGDGT and brGDGT) lipids, respectively. Here, we revisit these results using recent analytical developments – which have led to improved temperature calibrations and the discovery of new temperature-sensitive glycerol monoalkyl glycerol tetraethers (GMGTs) – and currently available proxy constraints. The isoGDGT assemblages support temperature as the dominant variable controlling TEX 86 values for most samples. However, contributions of isoGDGTs from land, which we characterize in detail, complicate TEX 86 paleothermometry in the late Paleocene and part of the interval between the Paleocene–Eocene Thermal Maximum (PETM; ∼ 56 Ma) and the Eocene Thermal Maximum 2 (ETM2; ∼ 54 Ma). Background early Eocene SSTs generally exceeded 20 ∘ C, with peak warmth during the PETM ( ∼ 26 ∘ C) and ETM2 ( ∼ 27 ∘ C). We find abundant branched GMGTs, likely dominantly marine in origin, and their distribution responds to environmental change. Further modern work is required to test to what extent temperature and other environmental factors determine their distribution. Published Arctic vegetation reconstructions indicate coldest-month mean continental air temperatures of 6–13 ∘ C, which reinforces the question of whether TEX 86 -derived SSTs in the Paleogene Arctic are skewed towards the summer season. The exact meaning of TEX 86 in the Paleogene Arctic thus remains a fundamental issue, and it is one that limits our assessment of the performance of fully coupled climate models under greenhouse conditions.